MODEL PEMBELAJARAN FIQIH BERBASIS MASALAH (Studi Fenomenologi Kegiatan Bahs al-Masa>’il di Madrasah Diniyyah Al-Hidayah Karangsuci Purwokerto) - syaefudin achmad (IAIN Purwokerto, 2020)
Abstract: The study of jurisprudence that has been held in Islamic educational institutions is considered not able to produce graduates who are ready to plunge in society to solve the problems in the realm of fiqih that appears in the community. One of the causes of this problem is the learning process whose instructional objectives do not lead to problem solving. Problem-based learning model can be one solution related to the problem. Problem-based learning model is a learning model that uses the problem as a learning base and demands active learners and uses a variety of intelligences. Madrasah Diniyyah Salafiyah Al-Hidayah has implemented a problem-based learning model through the activities of Bahs al-Masa>’il. The purpose of this research is to know the background of the activities of Bahs al-Masa>’il and to describe and analyze the problem-based learning model in the activities of Bahs al-Masa>’il in Madrasah Diniyyah Salafiyah Al-Hidayah.This research uses qualitative phenomenology approach. Techniques of data collection using observation, interviews, and documentation. The data collected from the technique was analyzed using phenomenological analysis. Keywords: Problem Based Learning Model, Bahs al-Masa>’il, Madrasah Diniyah